Legal Dynamics of Inheritance Across Religions Between Heirs and Beneficiaries in Indonesia - Nisa, Ardina Khoirun; Zulfahmi, Zulfahmi (Journal of Private and Commercial Law, 2025)
This article discusses the legal dynamics of inheritance of different religions between the testator and the heirs in Indonesia by comparing the inheritance law in the Civil Code and the Compilation of Islamic Law (KHI). The method in this article is legal research. This research is prescriptive, which is to provide an assessment of something that should be done. This research uses a case approach, namely by examining the legal reasons (ratio decidendi) used by the judge in the decision or determination. The results of this article conclude that according to inheritance law in the Civil Code, there is no recognition of religious differences as a barrier to inheritance, in other words, it is valid for people of different religions to become heirs or inherit. Whereas in the Compilation of Islamic Law (KHI), religious differences are a barrier for someone to get an inheritance from the heir. Although Islamic law and KHI do not recognize inheritance of different religions, the case of inheritance of different religions between the testator and the heir in Indonesia in several Supreme Court Decisions in Indonesia can be concluded that the Panel of Judges who decide cases regarding heirs of different religions with the testator can obtain inheritance through compulsory probate.